Soft Power Policy In Indonesia’s Overseas Politics for Peace in Afganistan - Rachman, Arief (Komunitas, 2021)
Indonesia's soft power policy in foreign policy for peace in Afghanistan is because at this time there are several similarities in religion which are the most easily accepted things in both countries. The problem under study is how to determine several criteria for the factors that encourage Indonesia to help bring peace in Afghanistan. The research method used is a combination method, a combination of qualitative and quantitative, with the process of collecting data through interviews and questionnaires to six experts in soft power efforts for peace in Afghanistan. Meanwhile, data analysis used the Delphi and Borda technique. The results show that seven reasons drive the need for Indonesia to use soft power for peace in Afghanistan, namely Indonesia's aspirations in realizing world peace (27%), Building the image of Indonesia as a peace bridge country (21%), Encouragement from Community Organizations (18 %), Studying Islam as the religion of Rahmatan lil Allamin (12%), Indonesia's proximity to Afghanistan and equality of identity (9%), Learning to handle conflict (8%) and Learning the values of Pancasila (5%).